(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2016)
Aim of this article is an overview of recent essays on the English works of Ugo Foscolo, which include numerous and many-sided literary and critic writings composed by the poet during his exile years in England. This late period of Foscolo’s activity has been greatly neglected and it is characterized by peculiarities and difficulties, both in terms of surviving documents and interpretation. We intend to look specifically into Foscolo’s works on Dante, also thanks to the opportunity to review Davide Colombo’s essay on Foscolo e i commentatori danteschi.